Engineering the title of scientific research: from methodological formulation to quality standards - Lachheb, Abdessalam; Boukhari, Fethi; Abdelkrim, Lachheb (Journal of Ecohumanism, 2025)
Scientific research plays a crucial role in achieving progress and excellence at all levels in all societies and nations. This is achieved through its foundations, methodologies, means, and tools, which help solve problems in any field of life. Therefore, any society striving for progress and intellectual and social advancement must prioritize scientific research.Scientific research in general, and research in the humanities and social sciences in particular, is conducted according to an integrated system of methodological and epistemological structural steps. This system forms a self-contained scientific research project within specific frameworks. The content of a scientific research project is revealed in its title, which serves as the research’s scientific identity and its most concise summary. Selecting and choosing an appropriate title is a vital step in the scientific research process, as it is the first thing that appears to the public and the reader.To explore this important step in scientific research (title selection), this research paper was written to examine its role in the quality of scientific research and to answer the following questions: What is a title? And what are the stages involved in selecting one? What are the requirements and specifications for a good title that accurately and clearly reflects the research?.